Nutrient export by clear cutting Eucalyptus grandis of different ages on two sites in Brazil - Bellote, A.F.J.; Dedecek, R.A.; Silva, H.D. da; Gava, J.L.; Menegol, O. (Center for International Forestry Research, 2001)
At two sites, where Eucalyptus grandis plantations were 7 and 12 years old, twelve dominant trees were cut and measured. The 12-year-old-trees were 29.4 m mean height, 19.9 cm diameter over bark and estimated volume 0.40 m3 tree-1. The 7 year-old trees were 30.7 m mean height, 20.6 cm diameter and estimated volume 0.49 m3 tree-1. Of total biomass, 92% was trunk (sapwood, heartwood and bark). Based on a population of 1500 trees ha-1, there is an export of biomass of 296 t ha-1 from 302 t ha-1 being produced, when the entire trunk is removed. When only commercial stems are removed, there is an export of 277 t ha-1. Within a whole tree, N is the nutrient present in greatest amount, followed by K, Ca, Mg and P. When parts of the tree are analysed, calcium is the nutrient present in greatest amount in bark. Phosphorus was not detected by the chemical analysis in heartwood in trees of 12 years of age, but it was present in trees aged 7 years. The amount of N and K extracted from soil by the trees is greater than the amount of these nutrients supplied by fertiliser, usually around 20 g plant-1 of N and 15 g plant-1of K2O. More than 50% of N, Ca and Mg are in the heartwood, sapwood and bark. Even if only commercial stems are taken from the plantation area, most of the nutrients will be exported.